2016
DOI: 10.1007/s12178-016-9320-4
|View full text |Cite
|
Sign up to set email alerts
|

Stemless shoulder arthroplasty—current results and designs

Abstract: Stemless shoulder arthroplasty was originally introduced in 2004 by a single manufacturer. Now, over a decade later, numerous designs are available outside the USA, but as yet, only one implant has been cleared by the Food and Drug Administration (FDA) and is available for use within the USA. Often referred to as Bcanal sparing,^these implants are designed for metaphyseal fixation to minimize humeral bone removal, avoid intraoperative and postoperative humeral fracture complications, and to decrease morbidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 29 publications
(31 reference statements)
0
44
0
2
Order By: Relevance
“…Stemless arthroplasty was introduced to decrease the rate of humeral stem-related complications such as humeral fracture, bone loss secondary to stress shielding, and osteolysis 209,210 . Proposed advantages include ease of revision 209,210 and management of arthritis associated with proximal humeral malunion 209,211 .…”
Section: Stemless Modular Shoulder Arthroplastymentioning
confidence: 99%
See 1 more Smart Citation
“…Stemless arthroplasty was introduced to decrease the rate of humeral stem-related complications such as humeral fracture, bone loss secondary to stress shielding, and osteolysis 209,210 . Proposed advantages include ease of revision 209,210 and management of arthritis associated with proximal humeral malunion 209,211 .…”
Section: Stemless Modular Shoulder Arthroplastymentioning
confidence: 99%
“…Proposed advantages include ease of revision 209,210 and management of arthritis associated with proximal humeral malunion 209,211 . Three prospective, randomized and nonrandomized studies 78,212,213 and 1 case-control study with early follow-up 214 demonstrated favorable clinical and radiographic results for both hemiarthroplasty and anatomic TSA.…”
Section: Stemless Modular Shoulder Arthroplastymentioning
confidence: 99%
“…The impacted corolla of the TESS prosthesis provides a peripheral metaphyseal anchoring[ 9 ]. This relatively stable fixation close to the cortical bone might explain why findings indicating a loosening were not noticed.…”
Section: Discussionmentioning
confidence: 99%
“…The Total Evolutive Shoulder System (TESS, Biomet-Zimmer, Warsaw, IN, United States) uses different sizes of an impaction-implanted 6-armed corolla for a peripheral metaphyseal anchoring close to the cortical bone. This method of fixation is different to those with a much more central anchoring within the metaphysis, e.g ., the threaded central cage of the Arthrex Eclipse (Arthrex, Karlsfeld, Germany) or the Simpliciti system with a nucleus and 3 fins for central impaction (Wright Medical, formerly Tornier, Montbonnot, France)[ 9 ]. The principle of a peripheral metaphyseal anchoring might influence the reconstruction of the individual anatomy of the proximal humerus.…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to mimic native bone stress and to preserve bone in the case of revision surgery, design modifications led to the fourth generation of shoulder arthroplasty with stemless or short-stem humeral components aimed at metaphyseal fixation [7,11,14]. In 2016, Harmer et al performed a systematic review of stemless and short-stem shoulder prosthesis and found that only one study reported results of anatomical shoulder replacement with an uncemented short stem [11].…”
Section: Short-stem Anatomical Shoulder Replacement-a Systematic Reviewmentioning
confidence: 99%